Prevalence and determinants of non-communicable diseases risk factors among reproductive aged women of Nepal: Results from Nepal Demographic Health Survey 2016 - Bista, Bihungum (PLoS One, 2020)
INTRODUCTION: Non-Communicable Diseases (NCDs) are the major killer diseases globally. They share the common risk factors such as smoking, harmful use of alcohol, physical inactivity, and low fruits/vegetable consumption. The clustering of these risk factors multiplies the risk of developing NCDs. NCDs affect women inequitably causing significant threats to the health of women and future generations. But, the distribution and clustering of NCDs risk factors among Nepalese women are not adequately explored yet. This study aimed to assess the clustering and socio-demographic distribution of major NCD risk factors in Nepalese women. METHODS: We used the data of 6,396 women age 15 to 49 years from the recent Nepal Demographic and Health Survey (NDHS). The survey applied a stratified multi-stage cluster sampling method to select the eligible women participants from across Nepal. We analyzed data using the multiple Poisson regression and reported the adjusted prevalence ratio (APR). RESULTS: A total of 8.9% of participants were current smokers, 22.2% were overweight and obesity and 11.5% of the participants were hypertensive. Around 6% of participants had co-occurrence of two NCDs risk factors. Smoking, overweight and obesity and hypertension were significantly associated with age, education, province, wealth index, and ethnicity. Risk factors were more likely to cluster in women of age40-49 years (ARR = 2.95, 95%CI: 2.58–3.38), widow/separated (ARR = 3.09; 95% CI:2.24–4.28) and among Dalit women (ARR = 1.34; 95% CI:1.17–1.55). CONCLUSION: This study found that NCDs risk factors were disproportionately distributed by age, education, socio-economic status and ethnicity and clustered in more vulnerable groups such as widow/separated women and the Dalit women.